CCD UBV(RI)KC photometry of the open clusters Juchert 9 and Berkeley 97. Issue 1 (27th February 2020) - Oralhan, İnci Akkaya; Michel, Raúl; Karsli, Yonca; Çakmak, Hikmet; Sung, Hwankyung; Karataş, Yüksel
Abstract: The CCD UBV ( RI ) KC photometry of the poorly studied open clusters Juchert 9 (Juc 9) and Berkeley 97 (Be 97), which are observed with the 0.84 m telescope at the San Pedro Mártir National Observatory, México has been analyzed. For the likely cluster members, we determined the reddenings, E(B‐V) = 0.82 ± 0.04 (Juc 9) and E(B‐V) = 0.87 ± 0.05 (Be 97), from the early type stars. Our distance moduli/distances for only ( B  −  V ) color are (V0 ‐M V, d [kpc]) = (13.40 ± 0.10, 4.8 ± 0.2 kpc) (Juc 9) and (12.40 ± 0.12, 3.0 ± 0.2 kpc) (Be 97), respectively. The Gaia DR2 distances are d  = 4.5 ± 1.2 kpc (Juc 9) and d  = 3.1 ± 0.7 kpc (Be 97) from the median parallaxes with σ ϖ / ϖ < 0.20, which are in good agreement with the photometric distances within the uncertainties. The solar abundance PARSEC isochrones give us the intermediate ages, 30 ± 10 Myr for Juc 9 and 100 ± 30 Myr for Be 97.